Village Chest Allocation Management in Pamarunan Village, Kahayan Tengah District, Pulang Pisau Regency - Riska; Sri Yuni; Yesika Yanuarisa (Journal Magister Ilmu Ekonomi Universtas Palangka Raya : GROWTH, 2020)
Management of Village Allocations in Pamarunan Village, Kahayan Tengah District, Pula Regency This study aims to describe and analyze the Management of Village Fund Allocations in Pamarunan Village, Kahayan Tengah District, Pulang Pisau Regency. Where in the description and analysis of this ADD uses agency theory (agency theory) contained in Good Corporate Governance which is based on Transparency, Accountability, Responsibility, and Justice. This study used qualitative research methods. Qualitative method is a research method based on the philosophy of postpsitivism, used to examine the condition of a natural object (as opposed to an experiment) where the researcher is the key instrument. From the results of this study it was concluded that the principles of transparency, accountability, responsibility, and equality have been well implemented into the Planning and Implementation, and Accountability of Village Fund Allocation, both technically and administratively and in accordance with the provisions of Permendagri No. 113 of 2014 concerning the management of village fund allocations. This provision also shows the commitment and decision making of stakeholders that the management of village fund allocations must meet the principles of Good Corporate Governance that must be implemented by the village government and the Desang Pisau Community.